Karakterisasi Morfologi Tumbuhan Mangrove di Pantai Mangkang Mangunharjo dan Desa Bedono Demak - Khusni, Ani Faridhatul; Hayati, Nur; Kusrinah, Kusrinah (AL-HAYAT: Journal of Biology and Applied Biology, 2018)
Mangrove plant is a local plant that specific roots, because it is generally only found on the beach is relatively small wavy. Mangrove has an important role as a natural shelter of the beach, because it has solid roots that can reduce waves and resist sediment. Bedono is one of the villages in Sayung District, Demak District. This location is chosen as a place of study because it has uniqueness. Mangunharjo Beach was chosen as a research location because it is influenced by chemical factors that have the same tendency, the interaction of land and waves, hence both need to be examined. This study aims to determine the morphological diversity of mangrove plants on the beach of Mangkang Mangunharjo and Bedono Village Demak. This research is an observational research with exploration and field observation technique. Sampling of mangrove plants was conducted at Mangkang Mangunharjo beach in Semarang and Bedono village of Demak. The study was conducted in January - April 2017. The results obtained from this study from Mangkang Mangunharjo Beach are Avicenia marina and Rhizopora mucronata. While 5 species are from Bedono Demak Village: Sonneratia caseolaris, Acanthus ilicofiolis, Rhizopora mucronata, Rhizopora apiculata, and Avicenia marina.